CHARACTERIZATION OF THE GENERATED SOLID WASTES IN CABINDA MUNICIPALITY, ANGOLA - Fernando do Rosario, José Baptista; Barrios Castillo, Grisel; Muto Lubota, David; Pedraza Garciga, Julio (Centro Azúcar Journal, 2014)
The aim of this study was to characterize municipal solid waste in the municipality of Cabinda by taking daily samples every five days during a period of one year. Methods such as direct observation, statistical analysis, and applying techniques such as interviews and surveys to the productive sector, the public and government managers. It was found that the municipal solid waste generated in the Cabinda town are 115,129.7 tons per day, they are composed of organic matter (57.4%), glasses (9.5%), paper (4.7%), plastics (6.7%), textiles (2.5%), metals (7.2%), sawdust (2.6%) and other materials (3.6%). This recommends the industrialization and also the reuse exploitation of the municipality solid waste, across the province and nearby provinces. Organic wastes requiring special projection use due to their high amount.